2013
DOI: 10.2166/aqua.2013.122
|View full text |Cite
|
Sign up to set email alerts
|

Assessing UV- and fluorescence-based metrics as disinfection byproduct precursor surrogate parameters in a water body influenced by a heavy rainfall event

Abstract: Although disinfection byproducts (DBPs) were discovered decades ago and surrogate parameters have been developed to track their precursors, the accuracy of these metrics in waters impacted by heavy rainfall events is largely unknown. We measured DBPs and their precursor surrogate parameters in a water body impacted by 28 cm of rain between 4/24/11 and 4/26/11. Raw waters collected from four locations within the water body from April to August 2011 were treated by coagulation and anion exchange. Ultraviolet abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…The fact that UV 254 was the most highly correlated surrogate parameter was an unexpected result given that similar studies showed fluorescence-based metrics were stronger (Granderson et al, 2013;Pifer et al, 2013). However, in the Granderson et al (2013) study, UV 254 was shown to be insensitive to chlorine dioxide, a treatment step not assessed in this work.…”
Section: Correlations Between Tthmfp and Precursor Surrogatesmentioning
confidence: 61%
See 2 more Smart Citations
“…The fact that UV 254 was the most highly correlated surrogate parameter was an unexpected result given that similar studies showed fluorescence-based metrics were stronger (Granderson et al, 2013;Pifer et al, 2013). However, in the Granderson et al (2013) study, UV 254 was shown to be insensitive to chlorine dioxide, a treatment step not assessed in this work.…”
Section: Correlations Between Tthmfp and Precursor Surrogatesmentioning
confidence: 61%
“…However, in the Granderson et al (2013) study, UV 254 was shown to be insensitive to chlorine dioxide, a treatment step not assessed in this work. Similarly, in the Pifer et al (2013) study, a heavy rainfall event produced an influx of dissolved iron, which biased the UV 254 measurements, but not the fluorescence. As such, we conclude that UV 254 is an excellent TTHMFP precursor surrogate for a diverse group of raw waters and alumcoagulated samples, similar to previous findings (Edzwald et al, 1985;Singer and Chang, 1989), but with notable exceptions (e.g., Granderson et al, 2013;Pifer et al, 2013).…”
Section: Correlations Between Tthmfp and Precursor Surrogatesmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, Corredor et al (2015) associated the catalytic redox properties of nanoparticles with colorimetric properties, thus allowing portable UV‐vis colorimeters to detect the presence and assess the catalytic surface activity of nanoparticles. Moreover, because organic DBP precursors have been associated with chromophoric characters, excitation–emission matrices (EEMs) or UV‐vis can be used to detect DBP FPs and monitor water quality (Pifer et al, 2014; Pifer and Fairey, 2014), assess the removal of DBP precursors (Do et al, 2015; Pifer and Fairey, 2012), and screen natural organic matter moieties as primary organic DBP precursors. In this work, we investigated optical parameter associations between light spectroscopic properties, choosing properties that represented the target properties indirectly, as they would otherwise need measurement with sophisticated instruments.…”
mentioning
confidence: 99%
“…Combined with potassium permanganate oxidation, aluminum sulfate coagulation reduced the demand of chlorine dioxide disinfectant and consequently minimized the formation of chlorite and chlorate (Sorlini et al 2014). The effects of heavy rainfall events on DBP mitigation by coagulation and anion exchange were investigated by Pifer et al (2014); 37-63% of chloroform precursors were removed. Though Water Environment Research, Volume 87, Number 10-Copyright © 2015 Water Environment Federation THMFP reduction was related to high DOC removal by coagulation in general (Gough et al 2014), infiltration of algal biomass with increasing phosphorus amendment made coagulation less effective for THMFP control (Mash et al 2014).…”
mentioning
confidence: 99%